The influence of macroeconomic factors on the Malaysian equity market / Jaafar Pyeman and Abdullah Sulaiman - Pyeman, Jaafar; Sulaiman, Abdullah (2004)
This study explores the influence of macroeconomic variables towards the stock market performance by utilizing the regression and correlation analyses on the movement of the indices at Kuala Lumpur Stock Exchange. The performance of the stock market will be measured based on the level of the indices stated by KLSE. This study was carried out for the period of five years from the year 1998 until 2002, a period where the Malaysian economy was experiencing various economic situations from booming economy up to the economic (financial) crisis. Now it has recovered from a recurrence of the 1997-1998 Asian economic crisis. The variables that were analyzed in this study are the macroeconomic variables as independent variables and the stock market performance as the dependent variable. There are three sub-variables under the macroeconomic factor in this analysis namely gross domestic product (GDP), interest rate and inflation rate. According to previous researches done, the gross domestic product, interest rates and the inflation rates were considered the most common elements that were taken into consideration. As compared to the previous studies on the impact of economic variables (gross domestic product, interest rate and inflation rate) on the stock market performance, there are some similarities or consistencies in terms of the findings. The results of this study suggest that tire macroeconomic fundamentals in Malaysia i.e., gross domestic product (GDP), inflation rate and interest rate influence the stock market performance differently. The major findings are (1) The gross domestic product is the most important determinant of the Malaysian stock market performance (2) The inflation rate is also the predominant force on the performance of share price in the market and (3) The interest rate has least impact on stock market performance. However, this study does not indicate a clear relation on the impact of inflation rate and interest rate on the stock market performance